Determinan Pertumbuhan Ekonomi Regional di Provinsi Maluku, 2005-2010 - Yerimias Manuhutu (EKO-REGIONAL, 2011)
Main purpose of this research is to evaluate and test variables that influencing regional economic growth in Maluku Province year 2004-2009 by using dynamic panel data method. Factors that influencing regional economic growth in Province of Maluku are private investment; government investment; infrastructure and labor. Result of this research indicating that panel of co-integration test with approach of parametric of group rho-statistic is 4,79 while group pp-statistic has a coefficient co-integration -12.18 whereas coefficient of co-integration by using group adf-statistic is -3.19. Probability of each examination indicating that variable with application of co-integration significant at level 1 percent only panel v-statistic at level 5 percents from seven panel model, got result that any variable of research co-integrated, in short term and long term has a positive direction to regional economic growth, meaning that if the independent variables increasing dependent variable will follow in same direction of movement. Keywords: regional economic growth, investment, panel dynamics